Prevalence of systemic complications of COVID-19 in critically ill patients: systematic review with meta-analysis - Namie Okino Sawada; Tiago Marques dos Reis; Patrícia Scotini Freitas; Camila Mendonça de Moraes; Bianca de Moura Peloso-Carvalho; Munyra Rocha Silva Assunção; Camila Maria Silva Paraizo Horvath; Ranile Santos Silva; Karina Dal Sasso Mendes (Revista Latino-Americana de Enfermagem, 2025)
Objective: to identify the prevalence of systemic complications of COVID-19 in critically ill patients, to estimate the clinical conditions that may have a worse prognosis when associated with COVID-19. Method: systematic review with meta-analysis of observational studies, based on the recommendations of the JBI Manual for Evidence Synthesis for systematic reviews of prevalence and incidence, in six databases and grey literature, period 2020 to 2024, languages Portuguese, English and Spanish. We identified 2393 publications. The selection, data extraction and methodological evaluation of the studies were carried out by two independent researchers. The meta-analysis was performed using the Freeman Tukey transformational random-effects statistical method. Results: ten papers were included. The meta-analysis of seven papers dealing with respiratory complications due to COVID-19 demonstrated a mean prevalence of 42%, (95% CI 0.2-0.66) with heterogeneity I2=97.4; the meta-analysis of 4 papers involving the prevalence of neurological complications due to COVID-19 showed an average prevalence of 62%, (95% CI 0.49- 0.74) with heterogeneity I2=87.4 and the meta-analysis of 8 studies showed a prevalence of mortality due to COVID-19 of 33%, (95% CI 0.23- 0.44) with heterogeneity I2=93.6. Conclusion: respiratory and neurological complications were the most prevalent in the reviewed studies. PROSPERO Registration: CRD42020214617.